Gum acacia/pectin/pullulan‐based edible film for food packaging application to improve the shelf‐life of ivy gourd. (2nd July 2022) - Suresh, Siva Nandhini; Puspharaj, Charumathi; Natarajan, Arunadevi; Subramani, Ramesh
Summary: Ternary blend of gum acacia/pectin/pullulan (GPPL) polysaccharide composite film was prepared using solution casting technique with the addition of different ratios of glycerol and sorbitol to increase plasticiser—polysaccharide interactions. The results showed that the film thickness, water contact angle, moisture content, solubility, tensile strength, elongation and anti‐microbial properties were in good agreement with already reported films in the literature. Composite film solution was used as a coating solution to improve the shelf‐life of ivy gourd ( Coccinia indica ). Weight loss, titrable acidity (TA), total soluble solids (TSS), anti‐oxidant, total phenolic content (TPC) and storage time were measured to check the efficiency of the coating solution. The obtained data shows a 35% increase in the shelf‐life of the ivy gourd during the storage period of 23 days. The anti‐microbial test showed that the prepared film/coating is more resistant against Pseudomonas aeruginosa due to the presence of pullulan. Therefore, our coating shows a significant increase in shelf‐life of ivy gourd up to 23 days of storage time. Thus, the prepared polysaccharide composite films in this study may be suitable for food packaging applications whereas the composite film solution can be used to improve the shelf‐life of various food products in the food industry. Abstract : Schematic representation of preparation and application of edible film and coating to improve the shelf‐life of ivy gourd.